Faktor–Faktor Yang Mempengaruhi Kinerja Umkm Bidang Kuliner Pada Masa Pandemi COVID – 19 - Keren Eunike; Louis Utama (Jurnal Manajerial Dan Kewirausahaan, 2021)
The purpose of this study is to find out whether Entrepreneurship Skills, Market Orientation, Sales Orientation, and Entrepreneurship Competence have an influence on the performance of SMEs in the culinary field. The population in this study is SMEs in the culinary sector. The sample used in this study were 50 respondens who owned MSMEs in the culinary field in Tanjung Duren, West Jakarta. The sampling technique used is non-probability sampling with purposive sampling method. Data collection was carried out using a Likert scale questionnaire. Overall the results of this study are that Entrepreneurship Skills have an influence on the performance of SMEs in the culinary field in Tanjung Duren, West Jakarta during the Covid-19 pandemic, Market Orientation has no effect on the performance of SMEs in the culinary field in Tanjung Duren, West Jakarta during the Covid-19 pandemic. 19, Sales Orientation has an influence on the performance of SMEs in the culinary field in Tanjung Duren, West Jakarta during the Covid-19 pandemic, Entrepreneurship Competence has an influence on the performance of SMEs in the culinary field in Tanjung Duren, West Jakarta during the Covid-19 pandemic.